Assessing the operational performance of Vodafone Ghana Company Limited in the Ghanaian Telecommunication Industry - Goni, Adams Abudu (2012)
A Thesis submitted to the of Institute of Distance Learning,Kwame Nkrumah University of Science and Technology in Partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration,